Índice de giro umbilical por ultrasonografía doppler en el segundo trimestre gestacional como marcador predictivo de complicaciones perinatales en los embarazos atendidos en el Hospital Regional de Loreto; 2021 - Bacca Pinto, Luis Ángel (2024)
Objectives: To determine whether prenatal Umbilical Gyrus Index (UGI) values through Doppler ultrasonography in the second gestational trimester are correlated with perinatal complications in pregnancies attended at the Regional Hospital of Loreto; 2021. Methodology: Observational, correlational, longitudinal, prospective study. Whose population will be pregnant women treated at the Regional Hospital of Loreto; 2021. Sampling will be probabilistic, simple random. The UGI will be calculated through Doppler ultrasound of prenatal control of pregnant women who are between weeks 16 and 23 of gestation and will be correlated with prenatal complications. Additionally, it will be considered to determine the sensitivity, specificity and predictive values of the UGI. Expected results: The expected results are that UGI will be associated with intrauterine growth restriction, presence of meconium fluid, APGAR scale less than 7 at five minutes, small fetus for gestational age, trisomy 21 and fetal death.